New Planning System and Hybrid MRP-JIT Production Control - Priyank S. Shah (Universitas Mulia, 2018)
Over the years, the production system has been largely controlled by the MRP (Material Requirement Planning, JIT (Timely) or OPT (Optimized Production Technology) paradigm. As expected, each of these paradigms has limited conditions operational effectiveness. A hybrid production planning and scheduling framework was developed for overcoming the problem of multi-stage, inventory-production systems by integrating MRP and JIT production. The combined MRP and JIT system can be a more effective manufacturing system use the best attributes of each production paradigm to accommodate the best planning features MRP and JIT's execution features are best for overcoming changing industry needs. That the goal is to find a detailed shop floor schedule, which determines the number of operations to be performed processed, at what time, and by which machine, so as to minimize the total production costs. That Integrated production systems eliminate some of the problems inherent in MRP & JIT and focus on set the goals, actions, and tasks of the entire organization to build competitiveness manufacturing capabilities, achieving manufacturing excellence, and maintaining a reasonable level growth.